2018
DOI: 10.4172/2167-0889.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Molecular Mechanisms during Cholestatic Liver Injury and Cholangiocarcinoma

Abstract: Cholestatic liver injury is characterized by damage induced on the biliary tree and cholangiocytes, the cells lining the biliary tree, thus they are termed “cholangiopathies”. Cholangiopathies include diseases such as Primary Biliary Cholangitis, Primary Sclerosing Cholangitis, Biliary Atresia and Cholangiocarcinoma. These pathologies lack viable therapies and most patients are diagnosed during late stage disease progression (with the exception of Biliary Atresia, which is found shortly after birth). The lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…However, the results of this study indicate the superior prognostic value of BAR compared to that of BLR. This discrepancy might stem from cholangiocarcinoma's potential to induce biliary obstruction and cholestatic liver injury, affecting FDG uptake of the liver [32,33]. Furthermore, our study revealed that FDG uptake in the normal liver tissue was influenced by cholangiocarcinoma tumor classification, suggesting that BAR might be a more suitable imaging parameter than BLR for estimating FDG uptake in the BM in patients with cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 77%
“…However, the results of this study indicate the superior prognostic value of BAR compared to that of BLR. This discrepancy might stem from cholangiocarcinoma's potential to induce biliary obstruction and cholestatic liver injury, affecting FDG uptake of the liver [32,33]. Furthermore, our study revealed that FDG uptake in the normal liver tissue was influenced by cholangiocarcinoma tumor classification, suggesting that BAR might be a more suitable imaging parameter than BLR for estimating FDG uptake in the BM in patients with cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 77%
“…Liver function test is widely used to detect liver condition in terms of ALT and AST, transaminase in hepatocytes and to indicate liver injury (33). Serum γ-GT is an indicator of biliary obstruction and hepatitis activity (34). Bile duct ligation (BDL), is the most common model used to induce cholestatic fibrosis in rodents (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…(7) The ppatient repeatedly had anemia and received packed red cell transfusion and Ursodeoxycholic acid (UDCA) for cholestasis as a hydrophilic bile acid, and it has been the most extensively studied putative pharmacological treatment for PSC. (8) Immunosuppressive agent and corticosteroid were given to this patient because of the autoimmune etiology of the disease. Biliary stenting was performed in this patient to help the stream of the bile.…”
Section: Discussionmentioning
confidence: 99%